Absorption spectrum of D2O between 10000–11000 cm-1. (December 2017) - Serdyukov, Viktor I.; Sinitsa, Leonid N.; Bykov, Alexander D.; Polovtseva, Elena R.; Scherbakov, Anatolii P.
Abstract: A study of the vibration-rotation absorption spectrum of the D2 O molecule in the range 10100–10800 cm -1 has been performed. The spectrum was recorded using a Fourier Transform Spectrometer with the spectral resolution of 0.05 cm -1 coupled to the multi-pass White-type cell providing an optical path length of 24 m. A light-emitting diode was used as the radiation source, giving a high brightness that resulted in an S/N ratio of measurements of about 10 4 . The rovibrational assignment of more than 920 lines was carried out, and the parameters of the spectral lines (i.e. centers, intensity and half-width) were determined by least-squares fitting of the Voigt contour parameters to the experimental data. A total of 530 rotational energy levels belonging to nine vibrational states (301), (103), (400), (221), (122), (320), (004), (023) and (042) and with maximum rotational quantum numbers J=16 and Ka=9 was determined. 101 energy levels were derived from the experiment for the first time. Highlights: Absorption spectrum of D2 O between 10000–11000 cm -1 . Line positions, intensities and energy levels of D2 O are measured. Results are compared with the predictions.